EFFECTIVE TECHNIQUES FOR IMPROVING PRONUNCIATION AND ACCENT - Nozimbek Evatovich Odilov (Ecomind Press, 2025)
Pronunciation and accent are critical components of spoken language proficiency, influencing intelligibility, communication effectiveness, and social integration. This thesis explores various techniques aimed at improving pronunciation and accent among language learners. Through a comprehensive review of phonetic training, auditory discrimination exercises, technological aids, and immersive practices, the study identifies which methods yield the most effective outcomes. Empirical evidence from experimental interventions highlights the importance of combining multiple approaches tailored to individual learner needs. The findings provide actionable recommendations for educators and learners seeking to optimize pronunciation and accent acquisition.
Keywords: Pronunciation improvement, Accent modification, Phonetic training, Auditory discrimination, Speech perception, Language learning techniques, Technology-assisted pronunciation, Speech recognition tools, Immersive language learning, Communicative language practice, Second language acquisition, Intelligibility in speech, Accent reduction methods, Pronunciation teaching strategies, Language learner confidence.